Ketaatan Wajib Pajak Orang Pribadi Dalam Melaporkan SPT Tahunan: Beserta Faktor-Faktor yang Mempengaruhinya - Muhamad Sirojudin; Mokhammad Ihsanuddin; Eni Nuraeni; Dirvi Surya Abbas (Jurnal Akuntansi, 2021)
Abstract This study examines the effect of understanding tax regulations, service quality, taxation, tax obligations, and application of e-filling on individual taxpayer compliance at KPP Pratama Kosambi. The dependent variable in this study is individual taxpayer compliance, and the independent variables in this study are understanding of tax regulations, service quality, tax sanction, willingness to pay taxes, and the application of filling. This research was conducted at KPP Pratama Kosambi Tax Service in the Tangerang area. The number of respondents in this study were 74 respondents. The sampling method in this study is incidental sampling. The result of this study conclude that the understanding of tax regulations has a negative and significant effect on taxpayer compliance. Service quality has a positive effect on individual taxpayer compliance. Tax sanctions have a positive and significant effect on individual taxpayer compliance, the desire to pay taxes has a negative and insignificant effect on individual taxpayer compliance. And the application of e-filling has no effect and is not significant on individual taxpayer compliance Keywords: Understanding of Tax Regulations, Service Quality, Tax Sanctions, Willingness to Pay Taxes, and Implementation of e-Filling